Effect of crown-to-implant ratio on the marginal bone level changes and implant survival – A systematic review and meta-analysis - Ninad Milind Padhye; Tabrez Lakha; Nadja Naenni; Mohit Kheur (Journal of Oral Biology and Craniofacial Research)
The purpose of the systematic review and meta-analysis was to analyze the existing evidence regarding the effect of crown-to-implant ratio (CIR) on the peri-implant crestal bone level change and implant survival. Randomized controlled clinical trials, prospective as well as retrospective studies with a minimum follow-up period of 12 months and 10 patients per group were included for this systematic review. Statistical analysis was performed to determine CIR effects on the peri-implant marginal bone level changes and implant survival. A total of 28 articles (14 prospective studies and 14 retrospective studies) from a database of 201 articles, with 2097 patients and 4350 implants, were included. A mean CIR ranging from 0.6 to 2.44 was presented by the study groups. A weighted mean implant loss of 0.19% per year and peri-implant marginal bone level change of 0.63 mm ± 0.55 over 46.8 ± 5.2 months was calculated from the included studies. The peri-implant marginal bone level change (p = 0.155) and the rate of implant loss (p = 0.245) showed a statistically insignificant difference between implant restorations of a high (>1.5:1) and low (<1.5:1) CIR. Within its limitations, this review concludes that a high (>1.5:1) or a low (<1.5:1) CIR does not significantly affect the peri-implant marginal bone level change and implant survival rate. However, until further evidence becomes available, extrapolation to long term clinical success cannot be ascertained.